Optimizing the acceleration of Cheddar cheese ripening using response surface methodology by microbial protease without altering its quality features - Alhelli, Amaal Mohammed; Mohammed, Nameer Khairullah; Khalil, Eilaf Suliman; Meor Hussin, Anis Shobirin (SpringerOpen, 2021)
Cheddar cheese proteolysis were accelerated employing Penicillium candidum PCA1/TT031 protease into cheese curd. In the present study, several of the significant factors such as protease purification factor (PF), protease concentration and ripening time were optimized via the response surface methodology (RSM). The ideal accelerated Cheddar cheese environment consisted of 3.12 PF, 0.01% (v/v) protease concentration and 0.6/3 months ripening time at 10 °C. The RSM models was verified to be the most proper methodology for the maintain of chosen Cheddar cheese. Under this experimental environment, the pH, acid degree value (ADV), moisture, water activity (aw), soluble nitrogen (SN)%, fat and overall acceptability were found to be 5.4, 6.6, 35%, 0.9348, 18.8%, 34% and 13.6, respectively of ideal Cheddar cheese. Furthermore, the predicted and experimental results were in significant agreement, which confirmed the validity and reliability of the suggested method. In spite of the difference between the ideal and commercial Cheddar cheese in the concentration of some of amino acids and free fatty acids, the sensory evaluation did not show any significant difference in aroma profile between them.